Liberation, Postmodernism, and Jacques Maritain: Confronting Individualism and Collectivism in the Twenty-First Century - Schultz, Walter J. (Toronto journal of theology, 2017)
Jacques Maritain, one of the twentieth century's leading Christian philosophers in the Thomist tradition, offers us a temporal ideal for a universal, inclusive struggle for justice and integral liberation while retaining the unique contribution and centrality of Jesus Christ. In agreement with Gustavo Gutiérrez, Maritain acknowledges the universality of grace throughout history, although carefully retaining a supernatural model allowing for a radical fulfillment of the Kingdom of God beyond every historical moment, thereby avoiding either a Marxist or a Fukuyamaesque pronouncement concerning the end of history. For Maritain, a concrete historical ideal encapsulates in a given historical climate the best possible actualization or temporal manifestation of the integral liberation of the whole person in community, signifying redemption and heralding the Kingdom of God to come. Focusing on the human person, rights, and the common good, Maritain stands on the concrete historical ideal of the holy freedom of the individual whom grace unites to God, which has become our global ideal since its inception within the concrete events of the European Enlightenment, and the French and American revolutions of the eighteenth century. Maritain contends that individualism and collectivism represent two sides of the same solipsistic coin curtailing the pursuit of authentic personalism. A nuanced and critical approach to liberation theology and postmodernism may enhance and develop Maritain's insights into the global perspective of the twenty-first century, thereby enabling us to glimpse what is essential for a truly human and Christian understanding of liberation and redemption in the twenty-first century.